Assessment of Training Course with Reliance on Problem Solving Approach for Mathematics Teachers (Atenas, 2021)
Training for secondary school teachers is a stimulus for the education transformation and it prepares the individuals for more activity and the flourish of their talents and creates a wide range of necessary skills and ideas for teaching. The aim of this study is to investigate the in-service training course which is based on the problem-solving approach in high school mathematics, and to measure the quality of education, using Kirkpatrick's four levels. Therefore, using a semi-experimental method, the problem-based training course was implemented for 62 male and female secondary school mathematics teachers. In this study, we used the questionnaire of in-service training course effectiveness evaluation which was developed based on Kirkpatrick's evaluation model. To analyze of the research, R software was used. The results showed that with regard to the t-test for the significance of each of these paths, the effects of these paths are significant (p